Tumor-educated Tregs drive organ-specific metastasis in breast cancer by impairing NK cells in the lymph node niche - Kos, Kevin; Aslam, Muhammad A.; van de Ven, Rieneke; Wellenstein, Max D.; Pieters, Wietske; van Weverwijk, Antoinette; Duits, Danique E.M.; van Pul, Kim; Hau, Cheei-Sing; Vrijland, Kim; Kaldenbach, Daphne; Raeven, Elisabeth A.M.; et al. (Cell reports (Cambridge), 2022)
Breast cancer is accompanied by systemic immunosuppression, which facilitates metastasis formation, but how this shapes organotropism of metastasis is poorly understood. Here, we investigate the impact of mammary tumorigenesis on regulatory T cells (Tregs) in distant organs and how this affects multi-organ metastatic disease. Using a preclinical mouse mammary tumor model that recapitulates human metastatic breast cancer, we observe systemic accumulation of activated, highly immunosuppressive Tregs during primary tumor growth. Tumor-educated Tregs show tissue-specific transcriptional rewiring in response to mammary tumorigenesis. This has functional consequences for organotropism of metastasis, as Treg depletion reduces metastasis to tumor-draining lymph nodes, but not to lungs. Mechanistically, we find that Tregs control natural killer (NK) cell activation in lymph nodes, thereby facilitating lymph node metastasis. In line, an increased Treg/NK cell ratio is observed in sentinel lymph nodes of breast cancer patients compared with healthy controls. This study highlights that immune regulation of metastatic disease is highly organ dependent. [Display omitted] •Mammary tumorigenesis drives systemic expansion of highly immunosuppressive Tregs•Tumor-educated Tregs promote lymph node (LN) metastasis but not lung metastasis•Tregs promote LN metastasis by local suppression of NK cells in the LN niche•LNs of breast cancer patients have elevated Treg and reduced NK cell accumulation Kos et al. demonstrate that breast cancer development is accompanied by systemic expansion of immunosuppressive regulatory T cells. The phenotype and function of tumor-educated Tregs are uniquely shaped by the local tissue environment. Consequently, tumor-educated Tregs impair local NK cell activity to enhance metastasis to lymph nodes, but not lungs.